The Relationship Between Emotion Regulation and Academic Stress in Class XII Students of Vocational High School Accounting Department: Hubungan Antara Regulasi Emosi Dengan Stres Akademik Pada Siswa Kelas XII Jurusan Akuntansi Sekolah Menengah Kejuruan - Refi Zyusifa; Ghozali Rusyid Affandi (Universitas Muhammadiyah Sidoarjo, 2021)
This study uses a type of correlational quantitative research. This study aims to determine whether there is a relationship between emotional regulation and academic stress in class XII students in Accounting in Antarctica 2 Sidoarjo Vocational School. The variables contained in this study are emotional regulations as independent variables and academic stress as dependent variables. This research was conducted at Antarctic Vocational School 2 Sidoarjo with a sample of 103 students using non probability sampling with accidental sampling techniques. Techniques in data collection using 2 Likert scales, namely the emotional regulation scale and academic stress scale. The results of this study are the existence of a significant relationship between emotional regulation and academic stress in students. Data analysis was carried out using Pearson correlation statistics with the help of SPSS ver. 24 for Windows. The results of the data analysis in this study showed a correlation coefficient of -0.569 with a significance value of 0.000 <0.05, this could be concluded that there was a negative relationship between emotional regulation and academic stress. This means that if the higher regulation of emotion, the lower the academic stress experienced by the Antarctic Vocational School 2 Sidoarjo, on the contrary if emotional regulation is lower, the felt academic stress will be higher.